04.03 Tgfβ-induced protein (tgfβi) is dysregulated in osteoarthritis. (1st March 2017) - Ruiz, Maxime; Maumus, Marie; Toupet, Karine; Fonteneau, Guillaume; Pers, Yves-Marie; Houard, Xavier; Berenbaum, Francis; Jorgensen, Christian; Noël, Danièle
Abstract : Backgrounds and objectives: Osteoarthritis (OA) is the most common rheumatic disease affecting all joint tissues and Transforming Growth Factor β (TGFβ) pathway dysregulation in bone marrow mesenchymal stem cells (MSCs) has been proposed to be involved in OA physiopathology. Based on secretome analysis of MSCs, we identified several TGFβ family members and focused our attention on Transforming Growth Factor β-Induced (TGFβI), a poorly studied extracellular matrix (ECM) component. Materials and methods: Human bone marrow MSCs were isolated from OA patients (OA-MSCs) and healthy donors (H-MSCs) while chondrocytes were isolated from OA patients (OA-CH). Chondrogenic differentiation of MSCs was induced in micropellet for 21 days. TGFβI expression was analysed by RT-qPCR and ELISA. Murine articular chondrocytes were isolated from 3 days old C57/BL6 mice and OA-like murine chondrocytes were obtained by addition of 1 ng/mL IL1β for 24 hour. Transfection of siRNA directed against TGFβI (siTGFβI) was performed using oligofectamine. The collagenase-induced murine model of OA was used for immunohistochemical analysis of cartilage and RNA extraction with TRIzol and acid phenol. Results: In humans, TGFβI mRNA expression was 2.5 fold lower in OA-MSCs than in H-MSCs and 10 fold lower in OA-MSCs than in OA-CH. We also found out that TGFβI was highly induced (by a 10 fold factor) during the first three days of chondrogenic differentiation but decreased to reach levels similar to those found in MSCs. In the mouse, immunohistochemical analysis revealed high expression of TGFβI in healthy cartilage as compared to OA cartilage. In murine MSCs, expression of TGFβI is 3.8 fold lower than in chondrocytes. In OA-like chondrocytes, characterised by reduced expression of anabolic markers and increased levels of catabolic markers, TGFβI mRNA levels were significantly lower than in healthy chondrocytes. Rapid decline of TGFβI expression was also observed in OA-like dedifferentiated chondrocytes. Finally, transfection of siTGFβI in murine chondrocytes resulted in alteration of their metabolic activity. Conclusion: Altogether, our results indicate that expression of TGFβI is higher in articular cartilage than in MSCs, and loss of TGFβI is associated with OA phenotype. TGFβI might be a key regulator of joint homeostasis involved in chondrogenesis and ECM integrity.